Análise da estabilidade de agregados do solo na conformação de vertente em uma topossequência no município de Gaurama/RS - Sandalowski, Cleusa Fátima (2013)
The soil is the base which supports several human elements and activities, such as agriculture and livestock. Therefore, it is a vital component of the ecosystem in which physical, chemical and biological processes and cycle transformations occur. In the municipality Gaurama, Rio Grande do Sul, and in other cities of our country, the local economy is strongly linked to agriculture activity being still responsible for an intense use of soil associated to a low or almost non-existence practice which aims to preserve the basic properties of natural resources leading to a great contribution for the ecosystem degradation. In such context, the proposition of studying slope management through analyses of soil aggregate stability in a toposequence has as objective to contribute for the importance of the comprehension that the pedological cover has in the slope morphological analysis as well as in the installation of three drillings and trenches above the slope in order to analyze morphological characteristics of the pedological volumes of the trenchings 1, 2 and 3, the distribution of particles, consistency limit and aggregate stability by humid via. This research was based on the deductive method. The granulometric analysis of the pedological volumes demonstrated similar characteristics between the T1 and T3 concerning the diameter of the particles, with the predominance of silt and clay fractions, as well as the similar values for the consistency limits and aggregate stability. In the T2, the sand fraction kept itself in balance with the others, not having any abrupt predominance of a granulometric fraction over the other ones. The consistency limits showed that the T2 presents a lower liquid and plastic limit which give it a higher susceptibility to erosive processes due to this soil profile which requires a lower amount of vain to reach a fluid behavior. The higher rates of soil aggregation occurred in the superficial pedological volumes. It was found that the V3 in Trench 2 had the lowest aggregate stability in the entire toposequence of the slope in this research, which shows that the modeling control process of the relief in the medium third and medium lower third of the slope receives a higher inference of this volume.